Development of Assemblr Edu-Based Augmented Reality Learning Media to Improve Learning Outcomes of Fifth Grade Students at SDN Kalibanteng Kidul 01 - Eprilia Hesvina; Eka Titi Andaryani (Postgraduate, University of Mataram, 2026)
This study aimed to examine the effectiveness of Augmented Reality (AR) learning media developed using the Assemblr Edu application for teaching food chain concepts in Grade V elementary school IPAS learning. This research uses a development approach with the ADDIE model with qualitative and quantitative methods. Quantitative data were obtained through pretest and posttest scores, while qualitative Data collection was carried out by distributing questionnaires, interviews and observations. The effectiveness of the AR learning media was analyzed using a normality test, paired sample t-test, and N-Gain analysis. The results showed that the pretest and posttest data were normally distributed. The paired sample t-test revealed a significant difference between students’ learning outcomes before and after using the AR learning media. N-Gain analysis showed moderate to high level improvements in student learning outcomes. In addition, classical mastery learning increased substantially after the implementation of the media. The results of this study show that AR-based learning media using Assemblr Edu is effective in improving elementary school students' understanding of the concept of the food chain. Therefore, the AR learning media developed can be used as an alternative innovative learning method in science learning. particularly for abstract topics that require concrete and interactive visualization.